Using hearing threshold-simulating noise to explore differences in speech intelligibility and listening effort between noise and quiet (Student Conference Proceedings, 2025)
Recent studies have shown significant differences in speech intelligibility and subjective listening effort between noisy and quiet environments. In this study, it was therefore investigated whether these differences can be explained by assuming that an internal noise limits speech perception in quiet at low levels. To explore this, psychometric functions of subjective listening effort and speech intelligibility were assessed in 18 normal-hearing participants using a noise spectrally matched to the hearing threshold. The hearing threshold-simulating noise (HTSN) at 70 dB SPL was compared to standard OLnoise at 60 dB SPL. The results indicate that differences between measurements in noise and quiet cannot fully be explained by assuming that soft speech is masked by internal noise different from that used during speech-in-noise tests. Future research should investigate potential cognitive effects beyond internal noise masking (HTSN) that influence speech intelligibility and listening effort in quiet.
Keywords: Listening effort; Speech intelligibility; hearing threshold-simulating noise